Micellar Curcumin: Pharmacokinetics and Effects on Inflammation Markers and PCSK‐9 Concentrations in Healthy Subjects in a Double‐Blind, Randomized, Active‐Controlled, Crossover Trial - Grafeneder, Juergen; Derhaschnig, Ulla; Eskandary, Farsad; Buchtele, Nina; Sus, Nadine; Frank, Jan; Jilma, Bernd; Schoergenhofer, Christian (Molecular nutrition & food research, 2022)
Scope: Preclinical models have demonstrated the anti‐inflammatory and lipid‐lowering effects of curcumin. Innovative formulations have been developed to overcome the poor bioavailability of native curcumin. The study hypothesizes that the bioavailability of micellar curcumin is superior to native curcumin and investigates the potential anti‐inflammatory and proprotein convertase subtilisin/kexin type 9 (PCSK9) concentration lowering effects. Methods and results: In this double‐blind, randomized, crossover trial, 15 healthy volunteers receive micellar or native curcumin (105 mg day−1) for 7 days with a ≥7 days washout period. Curcumin and metabolite concentrations are quantified by high‐performance liquid chromatography with fluorescence detection (HPLC‐FD), and pharmacokinetics are calculated. To analyze anti‐inflammatory effects, blood samples (baseline, 2 h, 7 days) are stimulated with 50 ng mL−1 lipopolysaccharides (LPS). Interleukin (IL)‐6, tumor‐necrosis factor (TNF‐α), and PCSK9 concentrations are quantified. Micellar curcumin demonstrates improved bioavailability (≈39‐fold higher maximum concentrations, ≈14‐fold higher area‐under‐the‐time‐concentration curve, p < 0.001) but does not reduce pro‐inflammatory cytokines in the chosen model. Subjects receiving micellar curcumin have significantly lower PCSK9 concentrations (≈10% reduction) after 7 days compared to baseline (p = 0.038). Conclusion: Micellar curcumin demonstrates an improved oral bioavailability but does not show anti‐inflammatory effects in this model. Potential effects on PCSK9 concentrations warrant further investigation. A micellar formulation of curcumin improves the absorption compared to native curcumin in 15 healthy volunteers. Intake of micellar curcumin reduces PCSK9 concentrations (≈10% reduction) after 7 days which could improve the blood lipid profile. In contrast to pre‐clinical studies, curcumin has no impact on the inflammatory response in our chosen model. Curcumin has an excellent safety profile.